ANALISIS KEBIJAKAN MITIGASI BENCANA DAERAH SESAR SADDANG - Alias, Muh.; Yunus, Mohammad (Jurnal Spasial, 2020)
The geographical location of West Sulawesi Province is right within the tectonic path of the ring of fire. The area of 810,405 km is just above the Saddang cesarian, active cesarian so that it has a high vulnerability to tectonic earthquakes and other disasters. The research purpose aimed at investigating the disaster mitigation policy of the Saddang cesarian area. The research method used was a qualitative descriptive approach aimed at providing a complete picture. Data collection techniques were collected through the techniques of observation, document studies, interviews with 2 key informants; Head of BPBD West Sulawesi Province, Head of BPBD Majene Regency, 4 main informants; Secretary of BPBD, Head of Prevention and Preparedness, Head of Rehabilitation and Reconstruction, Sulbar Provincial Health Office Employee, 2 additional community informants. The research results indicated that firstly, the standards, and policy objectives were implemented by passive and active mitigation in the form of disaster risk assessment of West Sulawesi (2016-2021). Secondly, policy resources are still minimal, such as health worker, health facility, vital facility for mitigation, and budget availability. Thirdly, characteristics of BNPB and BPBD as the implementing bodies were functioning as the controlling and coordinating bodies. Fourthly, TNI/Polri, Bappeda, Public Work Services, Health Services, Education Services were implementing organizations and Non-Governmental Organizations (NGOs) were the aid organizations. Fifthly, the communication among the organizations was not running actively, the attitudes of mitigation executant had high spirits and responsibilities. And lastly, social links are quite effective, as well as the economic and political factors that were less supportive of disaster mitigation programs.